Perceived impact of Kampung Teknologi RISDA program on rubber smallholders in Malaysia - Al-Awqati, Shakir Mahmood Jaafar (2018)
Currently, Malaysia is the world’s sixth largest producer of natural rubber (NR). To preserve sustainable occupation, National Agriculture Polices (NAP), government integration, with related agencies are targeting the employment of contemporary agricultural methods to increase NR production and livelihood of rubber smallholders, whom are the predominant contributors of NR production. Kampung Teknologi RISDA (KTR) program was implemented for this purpose by Rubber Industry Smallholders Development Authority (RISDA). The KTR respondents’ perception towards KTR program, KTR’s technology and extension activities were seen significant contributors to their perceived impact (outcome) of KTR program. Thus, to affirm the achievement of the stated goals an outcome program evaluation would be a sound procedure to explain KTR’s effectiveness extent on KTRs’ rubber respondents’ wellbeing. Owing to this, the study objectives are to: 1) identify the respondents’ perception level towards: KTR program, KTR’s technology and extension activities; 2) determine the respondents’ perceived impact level towards KTR program; 3) identify evidence of change (outcomes) related to KTR program impact; 4) identify the relationships between the respondents’ perception levels towards: KTR program, KTR’s technology and extension activities and the perceived impact; 5) identify the influences and relationships between selected socio-demographic factors, perception towards KTR program, perception towards KTR’s technology and perception towards extension activities and the respondents’ perceived impact of KTR program. Being quantitative and descriptive, the research’s questionnaire survey encompassed the states of Perak, Pahang, Selangor and Negeri Sembilan four (4) central states of Peninsular Malaysia, targeting 341 respondents among KTR participants. Owing to the geographical distribution, stratified sampling was involved to maintain subgroups’ characteristics and assert equal representation. The logic model as the evaluation tool, supported the independent and dependent variables selection. Applications of SPSS ver.22 and Microsoft Office 2013, Excel were involved to conclude further statistical results. The results showed that the majority of respondents (76.3%) were more than 51 years of age, where 59.8% were males and 40.2% were females. Furthermore, the study recorded that KTR respondents have a high perception levels towards KTR program, technology and extension activities, with total average means of (4.06), (3.92) and (4.1), respectively, which are substantial sings towards adoption. Whereas, the perceived KTR impact recorded moderate level with an overall average mean of (3.44). Correlations between perceptions towards KTR program, KTR’s technology and extension activities and perceived KTR impact were positive and significant. Finally, the Logistic regression results showed, that nearly all independent variables were positive and significant. However, level of education recorded negative and significant, and type of farming system was positive but non-significant to the perceived impact. To conclude, the respondent’s determination to embrace the new technology and adopting it was evident. In addition, to the program positive impact. Yet, they are advancing in age with income and level of education among other factors are contributors the program’s rapid outcomes. Therefore, further plans are required to support and increase their income, assessing such factors influencing the program’s goals achievements and to carry out more research to identify the absence of the young generation and for solutions to preserve the continuity of the industry.